Improving Soybean Germination and Nodule Development with Nitric Oxide-Releasing Polymeric Nanoparticles - Ana Cristina Preisler; Giovanna Camargo do Carmo; Rafael Caetano da Silva; Ana Luisa de Oliveira Simões; Juliana de Carvalho Izidoro; Joana Claudio Pieretti; Roberta Albino dos Reis; André Luiz Floriano Jacob; Amedea Barozzi Seabra; Halley Caixeta Oliveira (Plants)
Nitric oxide (NO) is a multifunctional signaling molecule in plants, playing key roles in germination, microbial symbiosis, and nodule formation. However, its instability requires innovative approaches, such as using nanoencapsulated NO donors, to prolong its effects. This study evaluated the impact of treating soybean (Glycine max) seeds with the NO donor S-nitrosoglutathione (GSNO), encapsulated in polymeric nanoparticles, on the germination, nodulation, and plant growth. Seeds were treated with free GSNO, chitosan nanoparticles with/without NO (NP CS-GSNO/NP CS-GSH, where GSH is glutathione, the NO donor precursor), and alginate nanoparticles with/without NO (NP Al-GSNO/NP Al-GSH). Chitosan nanoparticles (positive zeta potential) were smaller and released NO faster compared with alginate nanoparticles (negative zeta potential). The seed treatment with NP CS-GSNO (1 mM, related to GSNO concentration) significantly improved germination percentage, root length, number of secondary roots, and dry root mass of soybean compared with the control. Conversely, NP CS-GSH resulted in decreased root and shoot length. NP Al-GSNO enhanced shoot dry mass and increased the number of secondary roots by approximately threefold at the highest concentrations. NP CS-GSNO, NP Al-GSNO, and NP Al-GSH increased S-nitrosothiol levels in the roots by approximately fourfold compared with the control. However, NP CS-GSNO was the only treatment that increased the nodule dry mass of soybean plants. Therefore, our results indicate the potential of chitosan nanoparticles to improve the application of NO donors in soybean seeds.